Novel roles for Arabidopsis dynamin-related proteins DRP1A and DRP2B in resistance against Botrytis cinerea fungal infection. (31st December 2022) - Mc Gowan, Grant; Ekanayake, Gayani; Ingle, Robert A.; Heese, Antje
ABSTRACT: Arabidopsis DYNAMIN-RELATED PROTEIN1A ( At DRP1A) and At DRP2B are large GTPases that function together in endocytosis for effective cytokinesis, cell enlargement and development. A recent study shows that these DRPs contribute to ligand-induced endocytosis of the immune receptor FLAGELLIN SENSING2 ( At FLS2) to modulate flg22-immune signaling, and they are required for immunity against Pseudomonas syringae pv. tomato bacteria. Here, we demonstrate that atdrp1a and atdrp2b single mutants showed increased susceptibility to Botrytis cinerea indicating that At DRP1A and At DRP2B are necessary for effective resistance against this necrotrophic fungus. Thus, we expanded our limited understanding of clathrin endocytic accessory proteins in immunity against plant pathogens.